An asymptotic solving method for the periodic solution of a class of disturbed nonlinear evolution equation - 姚静荪 林万涛 杜增吉 莫嘉琪 (Chinese physics B, 2012)
A class of disturbed evolution equation is considered using a simple and valid technique. We first introduce the periodic traveling-wave solution of a corresponding typical evolution equation. Then the approximate solution for an original disturbed evolution equation is obtained using the asymptotic method. We point out that the series of approximate solution is convergent and the accuracy of the asymptotic solution is studied using the fixed point theorem for the functional analysis.